Efektivitas Friction Massage Terhadap Mengurangi Nyeri Pada Kasus Myofascial Trigger Point Syndrome Otot Upper Trapezius - Aditya Denny Pratama (Jurnal Ilmiah Fisioterapi, 2021)
Background: Myofascial trigger point syndrome is a musculoskeletal disorder characterized by the presence of a trigger point in a sensitive area within the skeletal muscle band linkages, if pressure is applied to the area it will cause specific pain at a point that is pressed (tenderness). Myofascial trigger point syndrome is influenced both by mechanism and by positioning factors. Myofascial trigger point syndrome upper trapezius muscle radiates along the upper back and neck, behind the ears and at the temples. Methods: The research method used is in the form of a case study with 1 patient who was given physiotherapy intervention and evaluation 4 times. To overcome the problem of muscle pain in bilateral trapezius m.upper in this study, using manual physiotherapy intervention therapy in the form of friction massage. Result: The results obtained, there was a decrease in tenderness in the upper trapezius muscle VAS 5 during the first evaluation to VAS 2 at the fourth evaluation with an average VAS value pre and post after one month for four interventions, namely 1.72. The MDC value (95) is 0.196 and the MCID range is 0.88-1.7, and 1.46-2.28. Conclusion: Based on these results, it can be concluded that physiotherapy intervention with the manual method of therapy, friction massage is considered effective in reducing pain in patients with myofascial trigger point syndrome, upper trapezius muscle with visual analogues scale (VAS) parameters. Keyword : Myofascial Trigger Point Syndrome, Manual Therapy, Friction Massage